CD44: A multifunctional mediator of cancer progression - Malak Hassn, Mesrati; Syafruddin, Saiful Effendi; Mohtar, M. Aiman; Syahir, Amir (Multidisciplinary Digital Publishing Institute, 2021)
CD44, a non-kinase cell surface transmembrane glycoprotein, has been widely implicated as a cancer stem cell (CSC) marker in several cancers. Cells overexpressing CD44 possess several CSC traits, such as self-renewal and epithelial-mesenchymal transition (EMT) capability, as well as a resistance to chemo- and radiotherapy. The CD44 gene regularly undergoes alternative splicing, resulting in the standard (CD44s) and variant (CD44v) isoforms. The interaction of such isoforms with ligands, particularly hyaluronic acid (HA), osteopontin (OPN) and matrix metalloproteinases (MMPs), drive numerous cancer-associated signalling. However, there are contradictory results regarding whether high or low CD44 expression is associated with worsening clinicopathological features, such as a higher tumour histological grade, advanced tumour stage and poorer survival rates. Nonetheless, high CD44 expression significantly contributes to enhanced tumourigenic mechanisms, such as cell proliferation, metastasis, invasion, migration and stemness; hence, CD44 is an important clinical target. This review summarises current research regarding the different CD44 isoform structures and their roles and functions in supporting tumourigenesis and discusses CD44 expression regulation, CD44-signalling pathways and interactions involved in cancer development. The clinical significance and prognostic value of CD44 and the potential of CD44 as a therapeutic target in cancer are also addressed.